PEMANFAATAN BUAH NIPAH (Nypa fruticans) SEBAGAI BAHAN BAKU PEMBUATAN SELAI - Fauzi Afrizal; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aim of this research was to determine the best ratio of sugar and fruit flesh of nipa palm suitable into a made of palm jam. This research was conducted by using a Completely Randomized Design Experiment, with four treatments and four repetitions. Treatments for a made of jam were N1 (fruit flesh of nipa palm 80% and sugar 20%), N2 (fruit flesh of nipa palm 70% and sugar 30%), N3(fruit flesh of nipa palm 60% and sugar 40%) and N4 (fruit flesh of nipa palm 50% and sugar 50%). The collected data was analyzed statistically by using ANOVA and DMRT in the 5% level. The best ratio of fruit flesh of nipa palm and sugar was N3 jam (fruit flesh of nipa palm 60% and sugar 40%) with moisture contens of 24.81%, ash 0.84%, total sugar 52.92% and viscosity 80.77%. The sensory test assessment of the chosen jam had a grey-yellow colored, palm aromatic, sweet tasted, unsticky textured and liked by panelist. Keywords : Jam, nipa palm, sugar, raw material